SOME ASPECTS OF ETIOPATHOGENESIS AND DIAGNOSIS OF NECROTIZING ENTEROCOLITIS IN CHILDREN - Леонид Владимирович Ким; Виктор Александрович Желев; Григорий Владимирович Слизовский; Эдуард Владимирович Девальд; Елена Владимировна Голикова; Андрей Леонидович Солнышко; Сергей Прокопьевич Ермоленко; Андрей Сергеевич Рейм (The Publishing House Medicine and Enlightenment, 2021)
Despite the fact that necrotizing enterocolitis (NEC) has been known for about two centuries, and intensive study of the disease has continued for the past 50 years, NEC remains an unsolved problem. Due to the emergence of new opportunities and technologies for the care of premature babies, interest in research has increased, the number of publications on NEC increased from 1-2 per year in the early 70s of the last century to more than 400 in 2020. Many researchers have devoted their entire careers to understanding, preventing, and treating NEC. However, the mortality rate has remained virtually unchanged over the past three decades. This review is a description of the currently known risk factors, aspects of the diagnosis and pathogenesis of the disease.